67 Are we missing patients with familial hypercholesterolaemia? assessment of lipid profile in patients referred via the primary PCI pathway. (June 2018) - Elgerray, Samir; Oleszkiewicz, Gregory; Haque, Zuhaina Noor; Uddin, Akhlaque
Abstract : Background: The advantages of statins have been indisputably demonstrated in secondary prevention and the greatest benefit has been established with early and intensive therapy following acute coronary syndrome. According to ESC and NICE guidelines, a lipid profile should be obtained as soon as possible after admission. Though recommendations are to commence therapy in all patients irrespective of lipid profile, levels still need to be assessed at baseline and 6–12 weeks. Project Aims: The main objectives were to improve assessment of lipid profile in the acute setting in all patients admitted with ST-elevation myocardial infarction (STEMI). Through this, there was capacity to aid in recognition and diagnosis of familial hypercholesterolaemia (FH). Methodology: A retrospective assessment of all patients referred via primary percutaneous intervention (PPCI) pathway to the Trent Cardiac Centre between April 2016 and April 2017. It was evaluated whether a random inpatient lipid profile was obtained, whether patients met biochemical Simon Broome criteria for FH (TC >7.5± LDL-C >4.9) and whether they were referred Lipid Clinic. Whether a statin was prescribed and whether they were followed up was also investigated. Results: From the 383 patients referred, 52 did not meet inclusion criteria. Of the remaining 331 patients, 20.2% (n=67) of patients did not have lipid profile checked as an inpatient. Of the 264 patients who had a lipid profile checked, 3% (n=8) met biochemical Simon Broome criteria and 0 were referred to lipid clinic. Abstract 67 Figure 1 Flow chart demonstrating project pathway, patients included and excluded and whether they were investigated and referred 41.3% (n=133) of patients had a follow up lipid profile. Only 32.2% (n=104) had both inpatient and follow up lipid profile There was good adherence to prescription of lipid lowering medication with 98.4% (n=326) of patients prescribed a statin. All patients that were not commenced on a statin had a documented reason. Conclusion and interpretation: These results demonstrate that more than 1 in 5 patients referred via the PPCI pathway did not have a random lipid profile checked. This shows a lack of adherence to guidelines. The 3% of patients meeting criteria for possible FH and were not referred to lipid clinic could have potential clinical implications in the future for patients and their families.